Breast Implant-Associated Anaplastic Large Cell Lymphoma With Bone Marrow Involvement. (7th April 2018) - Loghavi, Sanam; Medeiros, L Jeffrey; Javadi, Sanaz; Lin, Pei; Khoury, Joseph D; Nastoupil, Loretta; Hunt, Kelly K; Clemens, Mark W; Miranda, Roberto N
Abstract: We report a unique case of breast implant-associated anaplastic large cell lymphoma (BI-ALCL) with progressive systemic dissemination with extensive bone and bone marrow involvement. This case expands the clinical and pathologic spectrum of BI-ALCL and shows that although typically localized, BI-ALCL may present with disseminated disease with multiorgan involvement including bone and bone marrow. Disseminated BI- ALCL should be considered in the differential diagnosis of systemic ALCL. Unlike patients with localized disease, patients with disseminated BI-ALCL may benefit from systemic chemotherapy or immunotherapy. Level of Evidence: 5: